Logo world : symbol festival - Ibou, Paul (Zandhoven : Interecho Press, 1995)
Bass, Saul ; Behaeghel, Julien ; Beltran, Felix ; Bos, Ben ; Canovas, Eduardo ; Cato, Ken ; Consuegra, David ; Dheer, Sudarshan ; Duszek, Roman ; Fiszman, Gilles ; Fukuda, Shigeo ; Garamond, Jacques ; Grignani, Franco ; Gay, Clive ; Ibou, Paul ; Igarashi, Takenobu ; Kamekura, Yusaku ; Kapitzki, Herbert ; Keung, Kan-Tai ; Santschef, Stephan ; Taek-Kim, Young ; Kramer, Burton ; Kuhn, Klaus ; Langer, Helmut ; Matsunaga, Shin ; Minale, Marcello ; Mohr, Jack N. ; Müller-Brockmann, Josef ; Nagai, Kazumasa ; Rajlich, Jan ; Pamqvist, Kari ; Petit, Francesc ; Rand, Paul ; Miles-Runyan, Robert ; Stankowski, Anton ; Serov, Segei ; Serwatowski, Wladislaw ; Tartakover, David ; Vanmalderen, Luc ; Zapf, Hermann [et al.]
Review of the first Flanders World Logo Design Biennal in Ostend (Belgium) with visual presentations of the several disign exhibitions and the international design colloquuium. Thes compendium on the significance of logos and corporate identities prsent exclusive texts and pictures of a selection of some of the mostimportant graphic designers in the word.
boek